ANALISIS TERHADAP TRAIT AND FACTOR THEORY DAN IMPLIKASINYA DALAM LAYANAN BIMBINGAN KARIR - Raudatul Jannah; Dede Rahmat Hidayat (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2022)
Everyone dreams of a brilliant career in life. But in reality, in planning and determining a career, there are many problems, especially for teenagers who will enter adulthood, namely high school students. Many students have difficulty deciding which major, study program or job to choose after graduation. To overcome this, the role of BK teachers as counselors in schools is needed to carry out career guidance. Career guidance is a counseling service needed by individuals or students to help develop their potential and find their identity as well as plan and determine their careers. Career guidance can be carried out using a trait and factor theory approach, which is a counseling method that focuses on identifying individual/student traits or characters so that students can find their identity and do not hesitate in planning and choosing their careers. From several studies that have been carried out, it is proven that career guidance with a trait and factor approach is effective in helping reduce student doubts about career termination as well as improving students' understanding and career planning.